American exceptionalism in crime and punishment - Reitz, Kevin R. (Oxford University Press, 2018)
Introduction -- American exceptionalism : perspectives -- American exceptionalism in crime, punishment, and disadvantage : race, federalization, and politicization in the perspective of local autonomy / Nicola Lacey and David Soskice -- The concept of American exceptionalism and the case of capital punishment / David Garland -- Penal optimism : understanding American mass imprisonment from a Canadian perspective / Cheryl Marie Webster and Anthony N. Doob -- The complications of penal federalism : American exceptionalism or fifty different countries? / Franklin E. Zimring -- American exceptionalism in crime -- American exceptionalism in comparative perspective : explaining trends and variation in the use of incarceration / Tapio Lappi-Seppälä -- How exceptional is the history of violence and criminal justice in the United States? : variation across time and space as the keys to understanding homicide and punitiveness / Randolph Roth -- Making the state pay : violence and the politicization of crime in comparative perspective / Lisa L. Miller -- Comparing serious violent crime in the United States and England and Wales : why it matters, and how it can be done / Zelia Gallo, Nicola Lacey, and David Soskice -- American exceptionalism in community supervision : a comparative analysis of probation in the United States, Scotland, and Sweden / Edward E. Rhine and Faye S. Taxman -- American exceptionalism in parole release and supervision : a European perspective / Dirk van Zyl Smit and Alessandro Corda -- Collateral sanctions and American exceptionalism : a comparative perspective / Nora V. Demleitner -- Index